Replication and characterisation of genetic variants in the fibrinogen gene cluster with plasma fibrinogen levels and haematological traits in the Third National Health and Nutrition Examination Survey - Jeff, Janina M.; Brown-Gentry, Kristin; Crawford, Dana C. (Thrombosis and Haemostasis, 2012)
Previous genetic association studies of the fibrinogen gene cluster have identified associations with plasma fibrinogen levels. These studies are typically limited to plasma fibrinogen measured among European-descent populations. We sought to replicate previous well-known associations with fibrinogen variants and plasma fibrinogen. We then sought to identify and characterise novel associations with fibrinogen variants with plasma fibrinogen and several haematological traits in three racial/ethnic populations. We genotyped 25 single nucleotide polymorphisms (SNPs) in the fibrinogen gene cluster in 2,631 non-Hispanic whites, 2,108 non-Hispanic blacks, and 2,073 Mexican-Americans from the Third National Health and Nutrition Examination Survey (NHANES). We performed single SNP tests of association for plasma fibrinogen, mean platelet volume, platelet distribution width, platelet count, white blood cell count, and serum triglycerides. Five previously identified associations with plasma fibrinogen replicated in our study in non-Hispanic whites and blacks. We identified two novel associations between genetic variants and decreased plasma fibrinogen: rs2227395 (p=0.0007; non-Hispanic whites) and rs2070022 (p=0.001; Mexican-Americans). Several fibrinogen SNPs were also associated with haema-tological traits: rs6050 with decreased platelet distribution width in non-Hispanic whites; rs6050 and rs2066879 with decreased and increased platelet distribution width, respectively, in non-Hispanic whites; rs2227409 with increased mean platelet volume, rs2070017 with decreased platelet count, and rs6063 with increased platelet distribution width in non-Hispanic blacks; and rs4220 and rs2227395 with decreased white blood cell count, rs2227409 with increased platelet distribution width, rs2066860 and rs1800792 with increased and decreased triclyceride levels, respectively, and rs1800792 with decreased platelet counts in Mexican-Americans. We successfully replicated and identified novel associations with fibrinogen variants and plasma fibrinogen. These data confirm the importance of the fibrinogen gene cluster for plasma fibrinogen levels as well as suggest this gene cluster may have pleiotropic effects on haematological traits.
Keywords: Fibrinogen; pleiotropy; replication